Baslawısh klass oqıwshılarınıń kreativ kónlikpelerin rawajlandırıw máseleleri - Seytjanova, U.Q (SCIENCE and SOCIETY, 2024)
The article analyzes scientific research aimed at developing the creative skills of primary school students. The methods that develop the creative skills of younger students are complex. The article presents conclusions on the topic.
Keywords: creativity; personal motivation; formation of creative skill; creative process; intellectual